Patalogi Sosial Manusia Menurut Imam Al-Ghazali pada Kitab Ihya Ulumuddin - Siregar, Adnan Faris Naufal; Wantini, Wantini (Program Studi Bimbingan dan Konseling Islam, 2024)
This research examines Imam Al-Ghazali's thoughts on social pathology in the book Ihya Ulumuddin and its relevance to the contemporary social context. Using a qualitative approach and library research methods, this research analyzes the concept of social pathology according to Al-Ghazali, identifies the forms of social pathology he discusses, and explores the solutions he offers. The research results show that Al-Ghazali views social pathology as a deviation from Islamic moral and spiritual norms. He emphasized the importance of developing morals and spirituality as the main solution, with key concepts such as mahabbah (love), sincerity, khauf and raja' (fear and hope), tawakkal, gratitude, muraqabah (self-introspection), and repentance. This research finds that Al-Ghazali's thoughts are still relevant in dealing with contemporary social pathology, with an emphasis on strengthening spiritual and moral values ​​in the lives of individuals and society. The implication of this research is the need to integrate spiritual-moral perspectives in efforts to overcome social problems in the modern era.